Metabolic changes during development of Walker-256 carcinosarcoma resistance to doxorubicin - Todor, I.N.; Lukianova, N.Yu.; Shvets, Yu.V.; Lozovska, Yu.V.; Chekhun, V.F. (Experimental Oncology, 2015)
Aim: To study indices of energy metabolism, content of K+ and Mg++ both in peripheral blood and in Walker-256 carcinosarcoma during development of resistance to doxorubicin. Methods: Resistance of Walker-256 carcinosarcoma to doxorubicin has been developed through 12 subsequent transplantations of tumor after the chemotherapy. Parental strain was inhibited by drug by 65%, while transitional resistant substrains — by 30% and 2%, respectively. Determination of biochemical indices in blood serum and homogenates of tumor tissue, level of potassium, magnesium, lactate, glucose, activities of lactate dehydrogenase and glucose-6-phosphate dehydrogenase was performed with the help of biochemical and immune-enzyme analyzer GBG ChemWell 2990 (USA) using standard kits. Polarography was used to determine indices of mitochondrial oxidative phosphorylation. Study of mitochondrial membrane potential was carried out on flow cytometer Beckman Coulter Epics XL using dye JC-1. Results: It has been determined that development of drug resistance causes the decrease of K+, Mg++, glucose content in blood serum and increase of these indices in tumor tissue. At the same time, gradual tumor’s loss of sensitivity is characterized by decrease of glycolysis activity in it and activation of mitochondrial oxidative phosphorylation and pentose phosphate pathway of glucose degradation, which causes more intensive formation of NADPH. Conclusion: Development of drug resistance of tumor causes certain metabolic changes in organism and tumor. Further study of such changes will make possible to determine tumor and extratumor markers of resistance. Key Words: tumor, drug resistance, potassium, magnesium, glycolysis, pentose phosphate cycle, mitochondrial membrane potential.